Experimental Study on the Heat Transfer Characteristics of an Inclined Shell-and-Tube Phase-Change Thermal Energy Storage Unit - Zhang, Kun; He, Xiaoliang; Wang, Liangbi; Yu, Yan (Frontiers in Energy Research, 2022)
Detailed experimental investigation is presented for the heat transfer characteristics of an inclined shell-and-tube phase change thermal energy storage unit. For the case of inclined angle α = π/4, the solid-liquid interface presented a concave surface because the heat transfer can be affected not only by conduction in phase change material (PCM) domain, but also by natural convection significantly. The heat transfer rate increases with the increasing flow rate and inlet temperature of heat transfer fluid (HTF), but the flow rate of HTF has little effect on the charging process for the case of qv ≥ 40 L/h. The heat transfer rate of PCM above the HTF tube increases with the increase of inclined angle. The effects of inclined angle on the heat transfer rate can be not negligible due to the obvious natural convection in charging process.